Preparation process of eggshell glaze with shimmer effect
By preparing eggshell glaze with a shimmer effect, the problem of excessive gloss of ceramic tile glaze is solved, and the glaze effect is achieved that is wear-resistant, stain-resistant and anti-slip is improved, and visual comfort and user experience are improved.
Patent Information
- Application Number
- CN202411257261.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The gloss gloss of existing ceramic tiles are too high, resulting in visual fatigue and exposure of tiles defects, and lack of anti-slip and wear resistance.
A process of preparing eggshell glaze with a shimmer effect is adopted. By polishing the surface of the green body, preparing the glaze eggshell base glaze and protective glaze layer, inkjet printing pattern layer and sintering it in the kiln to form a wear-resistant, stain-resistant and anti-slip glaze surface.
The glossy effect of ceramic tile glaze is achieved, which enhances wear resistance, stain resistance and slip resistance, and improves visual comfort and user experience.
Smart Images

Figure CN119118709B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic glazes and relates to a preparation process of eggshell glaze with a micro-gloss effect. Background Art
[0002] In the past, ceramic tile surfaces have always pursued high gloss, and the higher the brightness, the better. Because high gloss can make the tile surface emit a dazzling luster, can strongly reflect the light of the surrounding environment, and even be able to reflect people, it is easy to create a brilliant and magnificent bright effect. However, if you look at too many bright products, it is very easy to make people excited, nervous and tired, and some people may even feel dizzy, especially under the reflection of light, which makes people uncomfortable on the one hand, and exposes the defects of the tile glaze itself on the other hand.
[0003] Under such circumstances, matte tiles came into being, among which the most representative ones are soft light, shimmer and satin. In addition to the visual comfort of light, shimmer tiles also have excellent anti-slip properties and a full texture. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation process of eggshell glaze with a shimmer effect. The prepared eggshell glaze with a shimmer effect has strong wear resistance, strong anti-fouling ability and good anti-slip effect.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A preparation process of eggshell glaze with a shimmer effect comprises the following steps:
[0007] S11. Green surface treatment:
[0008] Grind the surface of the green body and control the temperature at 80-90°C;
[0009] S12, preparing the glimmer eggshell base glaze slurry:
[0010] The raw materials of the glimmering eggshell glaze are mixed uniformly by weight percentage: 10-15% of nepheline, 30-35% of albite, 5-10% of kaolin, 2-5% of ball clay, 5-10% of calcined alumina, 5-10% of quartz, 20-25% of potassium feldspar, 3% of zinc oxide and 2-5% of dolomite, and then placed in a ball mill, and ground at a speed of 400-500 r / min for 1-2 hours, and then 42wt% of water, 0.20wt% of sodium carboxymethyl cellulose and 0.40wt% of sodium tripolyphosphate accounting for the raw materials of the glimmering eggshell glaze are added, and the speed is maintained to continue grinding for 7-9 hours, and the glaze is sieved and iron is removed by a magnetic iron remover to prepare a glimmering eggshell glaze slurry;
[0011] S13, preparing the shimmering eggshell bottom glaze layer:
[0012] The surface of the green body is coated with a low-gloss eggshell base glaze slurry by a glazing process. The glaze water specific gravity is 1.82-1.88 g / mL and the glazing amount is 80-110 g / m 2 , forming a shimmering eggshell enamel layer;
[0013] S14, preparing pattern layer:
[0014] The matte ink is sprayed on the surface of the shimmer eggshell base glaze layer by intelligent inkjet printing to form a pattern layer;
[0015] S15, preparing the shimmering eggshell protective glaze slurry:
[0016] The raw materials of the glimmer eggshell protective glaze are mixed uniformly by weight percentage: 15-20% of albite, 15-20% of potassium feldspar, 7-14% of modified kaolin, 3-5% of zinc oxide, 5-8% of dolomite, 10-15% of low-temperature frit, 10-13% of modified wollastonite, 5-10% of strontium carbonate and 10-15% of barium carbonate, and then placed in a ball mill, and ground at a speed of 400-500 r / min for 1-2 hours, and then 42wt% of water, 0.20wt% of sodium carboxymethyl cellulose and 0.40wt% of sodium tripolyphosphate accounting for the raw materials of the glimmer eggshell protective glaze are added, the speed is maintained and the grinding is continued for 7-9 hours, and a magnetic iron remover is used to remove iron to prepare a glimmer eggshell protective glaze slurry;
[0017] S16, preparation of shimmering eggshell protective glaze layer:
[0018] The glaze slurry is applied with a micro-gloss eggshell protective glaze slurry on the surface of the pattern layer through the glaze spraying process. The glaze water specific gravity is 1.25-1.35g / mL and the glaze spraying amount is 250-350g / m 2 ;
[0019] S17, sintering:
[0020] The eggshell glaze with the micro-gloss effect is prepared by firing in a kiln at 1150-1170° C. for 43-47 minutes.
[0021] As a preferred technical solution of the present invention, in step S15, the preparation process of the modified wollastonite is as follows:
[0022] S21, treating the glass fiber by irradiation;
[0023] S22, adding glass fiber to an aqueous solution containing 5% by mass of a silane coupling agent, stirring and mixing, soaking at 50 to 55° C. for 10 to 15 minutes, taking out, filtering and drying, and obtaining modified glass fiber;
[0024] S23. Mix wollastonite and modified glass fiber in a mass ratio of (10-11): (1-3), heat to 70-80°C, stir at a speed of 350-450 r / min for 4-5 hours, dry with hot air at 90-100°C for 11-15 hours, and grind with a ball mill at a speed of 400 r / min for 3-4 hours to obtain the modified wollastonite.
[0025] As a preferred technical solution of the present invention, in step S15, the preparation process of the modified kaolin is as follows:
[0026] S31, at a temperature of 70 to 80° C., ultrasonically dispersing kaolin and water at a power of 200 to 300 W to obtain a kaolin dispersion;
[0027] S32, adjusting the pH of the kaolin dispersion to 7.5-8.5 with an organic base;
[0028] S33, continue to add castor oil alkyd resin, wherein the mass ratio of kaolin, water and castor oil alkyd resin is (4-6):11:(2-4), heat to 80-90°C, continue stirring for 2-3h, let stand for aging for 10h, dry for 3-5h, then heat to 240-260°C and keep warm for 2-3h, cool to 60°C and place in a planetary ball mill for ball milling, and pass through a 600-mesh sieve to obtain the modified kaolin.
[0029] As a preferred technical solution of the present invention, in step S15, the chemical composition of the low-temperature melt is: SiO2: 54.6%, Al2O3: 12.01%, CaO: 6.85%, MgO: 4.57%, K2O: 5.18%, Na2O: 2.08%, ZnO: 6.34%, BaO: 8.37%.
[0030] As a preferred technical solution of the present invention, in step S21, the irradiation power of the irradiation treatment is 350-450W, and the irradiation time is 1-2h.
[0031] As a preferred technical solution of the present invention, in step S22, the silane coupling agent is one of KH-570, KH-792, and DL-602.
[0032] As a preferred technical solution of the present invention, in step S22, the solid-to-liquid ratio of the glass fiber to the aqueous solution of the silane coupling agent is 1:10 g / mL.
[0033] As a preferred technical solution of the present invention, in step S32, the organic base is one of triethylamine and pyridine.
[0034] Beneficial effects of the present invention:
[0035] The present invention changes the surface properties of glass fiber through irradiation treatment, improves the surface activity of glass fiber, enhances its softness and dispersibility, and facilitates the subsequent preparation of composite materials with wollastonite to enhance the bonding force between glass fiber and wollastonite; after wollastonite is treated with a silane coupling agent, since the surface of glass fiber contains a large number of siloxy groups (Si-OH), the silane groups (Si-OR) in the silane coupling agent can react with Si-OH to form a chemical bond Si-O-Si, thereby firmly combining the silane coupling agent with the surface of glass fiber. The formation of this chemical bond significantly improves the wettability and adhesion of the glass fiber surface, and at the same time, through ball milling, The silane coupling agent can react with these active groups on the surface of wollastonite through its silane group, so as to form a kind of "molecular bridge" between the glass fiber and wollastonite, with one end combining with the siloxy group on the surface of the glass fiber and the other end combining with the active group on the surface of wollastonite, or closely fitting with the surface of wollastonite through physical adsorption, which greatly enhances the interfacial bonding force between the glass fiber and wollastonite, so that the modified wollastonite can better improve the overall wear resistance of the composite material.
[0036] Modifying kaolin with castor oil alkyd resin can improve the dispersibility of kaolin in ceramic glazes, making it easier to distribute evenly, forming a uniform and stable glaze slurry, and improving the fluidity of the slightly glossy eggshell protective glaze slurry; at the same time, the enhanced adhesion of kaolin modified with castor oil alkyd resin helps prevent the glaze layer from peeling or cracking during use, and enhances the hardness and wear resistance of the glaze layer. Moreover, since castor oil alkyd resin is attached to the surface of kaolin, castor oil alkyd resin can form a continuous film layer during the sintering process, covering the surface of the ceramic. This film layer not only has a protective effect, but also gives the ceramic products a good touch and visual effect.
[0037] The existing eggshell base glaze generally has a shimmer surface with a gloss of 3 to 3.5 degrees, and the application amount is usually 500 to 700 g / m 2 Around, matte ink is mainly used to cover the shimmer eggshell base glaze to make the surface gloss more uniform and delicate; the shimmer eggshell protective glaze in the present invention needs to have high permeability to avoid the application of a large amount of eggshell protective glaze resulting in a hazy glaze surface or insufficient transparency and affecting the design transparency effect. The application amount of the shimmer eggshell protective glaze in the present invention is 20-30% more than that of conventional protective glaze. The glazing process of the shimmer eggshell protective glaze is used to achieve full coverage of the shimmer eggshell base glaze, ensuring the close combination of the shimmer eggshell base glaze and the shimmer eggshell protective glaze, ensuring the transparency effect of the shimmer eggshell protective glaze, and also avoiding excessive application of the shimmer eggshell protective glaze to affect the three-dimensional effect of the brick surface.
[0038] The invention prepares an eggshell glaze with a shimmer effect. The eggshell glaze ceramic tile has many patterns on the surface and a high friction coefficient. It can maintain an excellent anti-skid effect even in a humid environment, and has strong wear resistance, strong anti-fouling ability and good anti-skid effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0040] Figure 1 This is a surface effect diagram of the eggshell glaze with a shimmer effect prepared in Example 1. DETAILED DESCRIPTION
[0041] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0042] In the following examples and comparative examples:
[0043] Castor oil alkyd resin was purchased from Nantong Fangxin Chemical Co., Ltd., with the product number FX-6703;
[0044] The chemical composition of the low-temperature frit is: SiO2: 54.6%, Al2O3: 12.01%, CaO: 6.85%, MgO: 4.57%, K2O: 5.18%, Na2O: 2.08%, ZnO: 6.34%, BaO: 8.37%.
[0045] Example 1
[0046] By weight percentage, the raw materials of the shimmering eggshell base glaze are: nepheline 10%, albite 35%, kaolin 5%, ball clay 2%, calcined alumina 10%, quartz 5%, potassium feldspar 25%, zinc oxide 3% and dolomite 5%;
[0047] Raw materials of the shimmering eggshell protective glaze: 15% albite, 20% potassium feldspar, 7% modified kaolin, 5% zinc oxide, 5% dolomite, 15% low-temperature frit, 13% modified wollastonite, 5% strontium carbonate and 15% barium carbonate;
[0048] Preparation of modified wollastonite:
[0049] S21, irradiating the glass fiber at a power of 350 W for 1 h;
[0050] S22, adding glass fiber to an aqueous solution containing 5% by mass of KH-570, stirring and mixing, soaking at 50° C. for 10 min, taking out, filtering and drying to obtain modified glass fiber, wherein the solid-to-liquid ratio of the glass fiber to the aqueous solution of the silane coupling agent is 1:10 g / mL;
[0051] S23, mixing wollastonite and modified glass fiber in a mass ratio of 10:1, heating to 70°C and stirring at a speed of 350 r / min for 4 hours, drying with hot air at 90°C for 11 hours, and then grinding with a ball mill at a speed of 400 r / min for 3 hours to obtain the modified wollastonite.
[0052] Preparation of the modified kaolin:
[0053] S31, at a temperature of 70° C., ultrasonically dispersing kaolin and water at a power of 200 W to obtain a kaolin dispersion;
[0054] S32, adjusting the pH of the kaolin dispersion to 7.5 with triethylamine;
[0055] S33, continue to add castor oil alkyd resin, wherein the mass ratio of kaolin, water and castor oil alkyd resin is 4:11:2, raise the temperature to 80°C, continue stirring for 2 hours, let stand for aging for 10 hours, dry for 3 hours, then raise the temperature to 240°C and keep warm for 2 hours, cool to 60°C and place in a planetary ball mill for ball milling, and pass through a 600-mesh sieve to obtain the modified kaolin.
[0056] Preparation of eggshell glaze with shimmer effect:
[0057] S11. Green surface treatment:
[0058] The surface of the green body is polished and the temperature is controlled at 80°C;
[0059] S12, preparing the glimmer eggshell base glaze slurry:
[0060] The raw materials of the shimmer eggshell glaze are mixed evenly and placed in a ball mill. After grinding at a speed of 400 r / min for 1 hour, 42 wt% of water, 0.20 wt% of sodium carboxymethyl cellulose and 0.40 wt% of sodium tripolyphosphate accounting for the raw materials of the shimmer eggshell glaze are added. The speed is maintained and grinding is continued for 7 hours. The mixture is sieved and iron is removed by a magnetic iron remover to prepare a shimmer eggshell glaze slurry.
[0061] S13, preparing the shimmering eggshell bottom glaze layer:
[0062] The surface of the green body is coated with a low-gloss eggshell base glaze slurry by glazing process. The glaze water specific gravity is 1.82g / mL and the glaze amount is 80g / m 2 , forming a shimmering eggshell enamel layer;
[0063] S14, preparing pattern layer:
[0064] The matte ink is sprayed on the surface of the shimmer eggshell base glaze layer by intelligent inkjet printing to form a pattern layer;
[0065] S15, preparing the shimmering eggshell protective glaze slurry:
[0066] The raw materials of the shimmer eggshell protective glaze are mixed evenly, and then placed in a ball mill, and ground at a speed of 400 r / min for 1 hour, and then 42 wt% of water, 0.20 wt% of sodium carboxymethyl cellulose and 0.40 wt% of sodium tripolyphosphate accounting for the raw materials of the shimmer eggshell protective glaze are added, and the speed is maintained and the grinding is continued for 7 hours, and the iron is removed by a magnetic iron remover to prepare a shimmer eggshell protective glaze slurry;
[0067] S16, preparation of shimmering eggshell protective glaze layer:
[0068] The glaze slurry is applied with eggshell protection on the surface of the pattern layer through the glaze spraying process. The specific gravity of the glaze is 1.25g / mL and the glaze spraying amount is 250g / m 2 ;
[0069] S17, sintering:
[0070] The eggshell glaze with the micro-gloss effect is prepared by firing in a kiln at 1150° C. for 43 minutes.
[0071] Example 2
[0072] By weight percentage, the raw materials of the shimmering eggshell base glaze are: nepheline 12%, albite 33%, kaolin 8%, ball clay 3%, calcined alumina 8%, quartz 8%, potassium feldspar 22%, zinc oxide 3% and dolomite 5%;
[0073] Raw materials of the shimmering eggshell protective glaze: 17% albite, 17% potassium feldspar, 10% modified kaolin, 4% zinc oxide, 7% dolomite, 13% low-temperature frit, 11% modified wollastonite, 6% strontium carbonate and 13% barium carbonate;
[0074] Preparation of modified wollastonite:
[0075] S21, irradiating the glass fiber at a power of 400 W for 1.5 h;
[0076] S22, adding glass fiber to an aqueous solution containing 5% by mass of KH-570, stirring and mixing, soaking at 53° C. for 13 min, taking out, filtering and drying to obtain modified glass fiber, wherein the solid-to-liquid ratio of the glass fiber to the aqueous solution of the silane coupling agent is 1:10 g / mL;
[0077] S23, mixing wollastonite and modified glass fiber in a mass ratio of 10.5:2, heating to 75°C and stirring at a speed of 400 r / min for 4.5 hours, drying with 5°C hot air for 13 hours, and then grinding with a ball mill at a speed of 400 r / min for 3.5 hours to obtain the modified wollastonite.
[0078] Preparation of the modified kaolin:
[0079] S31, at a temperature of 75° C., ultrasonically dispersing kaolin and water at a power of 250 W to obtain a kaolin dispersion;
[0080] S32, adjusting the pH of the kaolin dispersion to 8 with triethylamine;
[0081] S33, continue to add castor oil alkyd resin, wherein the mass ratio of kaolin, water and castor oil alkyd resin is 5:11:3, heat to 85°C, continue stirring for 2.5 hours, let stand for aging for 10 hours, dry for 4 hours, then heat to 250°C and keep warm for 2.5 hours, cool to 60°C and place in a planetary ball mill for ball milling, and pass through a 600-mesh sieve to obtain the modified kaolin.
[0082] Preparation of eggshell glaze with shimmer effect:
[0083] S11. Green surface treatment:
[0084] The surface of the green body is polished and the temperature is controlled at 85°C;
[0085] S12, preparing the glimmer eggshell base glaze slurry:
[0086] The raw materials of the shimmer eggshell glaze are mixed evenly and placed in a ball mill. After grinding at a speed of 450 r / min for 1.5 hours, 42 wt% of water, 0.20 wt% of sodium carboxymethyl cellulose and 0.40 wt% of sodium tripolyphosphate accounting for the raw materials of the shimmer eggshell glaze are added, and the speed is maintained to continue grinding for 8 hours, and the glaze is sieved and iron is removed with a magnetic iron remover to prepare a shimmer eggshell glaze slurry;
[0087] S13, preparing the shimmering eggshell bottom glaze layer:
[0088] The surface of the green body is coated with a low-gloss eggshell base glaze slurry by a glazing process. The glaze water specific gravity is 1.85g / mL and the glazing amount is 100g / m 2 , forming a shimmering eggshell enamel layer;
[0089] S14, preparing pattern layer:
[0090] The matte ink is sprayed on the surface of the shimmer eggshell base glaze layer by intelligent inkjet printing to form a pattern layer;
[0091] S15, preparing the shimmering eggshell protective glaze slurry:
[0092] The raw materials of the shimmer eggshell protective glaze are fully mixed and then placed in a ball mill. After grinding at a speed of 450 r / min for 1.5 hours, 42 wt% of water, 0.20 wt% of sodium carboxymethyl cellulose and 0.40 wt% of sodium tripolyphosphate accounting for the raw materials of the shimmer eggshell protective glaze are added, and the speed is maintained and the grinding is continued for 8 hours. The magnetic iron remover is used to remove iron to prepare the shimmer eggshell protective glaze slurry;
[0093] S16, preparation of shimmering eggshell protective glaze layer:
[0094] The glaze slurry is applied with a micro-gloss eggshell protective glaze slurry on the surface of the pattern layer through the glaze spraying process. The glaze water specific gravity is 1.30g / mL and the glaze spraying amount is 300g / m 2 ;
[0095] S17, sintering:
[0096] The eggshell glaze with the shimmering effect is prepared by firing in a kiln at 1160° C. for 45 minutes.
[0097] Example 3
[0098] By weight percentage, the raw materials of the shimmering eggshell base glaze are: 15% nepheline, 30% albite, 10% kaolin, 5% ball clay, 5% calcined alumina, 10% quartz, 20% potassium feldspar, 3% zinc oxide and 2% dolomite;
[0099] Raw materials of the shimmering eggshell protective glaze: 20% albite, 15% potassium feldspar, 14% modified kaolin, 3% zinc oxide, 8% dolomite, 10% low-temperature frit, 10% modified wollastonite, 10% strontium carbonate and 10% barium carbonate;
[0100] Preparation of modified wollastonite:
[0101] S21, irradiating the glass fiber at a power of 450 W for 2 h;
[0102] S22, adding glass fiber to an aqueous solution containing 5% by mass of KH-792, stirring and mixing, soaking at 53° C. for 13 min, taking out, filtering and drying to obtain modified glass fiber, wherein the solid-to-liquid ratio of the glass fiber to the aqueous solution of the silane coupling agent is 1:10 g / mL;
[0103] S23, mixing wollastonite and modified glass fiber in a mass ratio of 11:3, heating to 80°C and stirring at a speed of 450 r / min for 5 h, drying with hot air at 100°C for 15 h, and then grinding with a ball mill at a speed of 400 r / min for 4 h to obtain the modified wollastonite.
[0104] Preparation of the modified kaolin:
[0105] S31, at a temperature of 80° C., ultrasonically dispersing kaolin and water at a power of 300 W to obtain a kaolin dispersion;
[0106] S32, adjusting the pH of the kaolin dispersion to 8.5 with triethylamine;
[0107] S33, continue to add castor oil alkyd resin, wherein the mass ratio of kaolin, water and castor oil alkyd resin is 6:11:4, heat to 90°C, continue stirring for 3 hours, let stand for aging for 10 hours, dry for 5 hours, then heat to 260°C and keep warm for 3 hours, cool to 60°C and place in a planetary ball mill for ball milling, and pass through a 600-mesh sieve to obtain the modified kaolin.
[0108] Preparation of eggshell glaze with shimmer effect:
[0109] S11. Green surface treatment:
[0110] The surface of the green body is polished and the temperature is controlled at 90°C;
[0111] S12, preparing the glimmer eggshell base glaze slurry:
[0112] The raw materials of the shimmer eggshell glaze are mixed evenly and placed in a ball mill, and ground at a speed of 500 r / min for 2 hours, and then 42 wt% of water, 0.20 wt% of sodium carboxymethyl cellulose and 0.40 wt% of sodium tripolyphosphate are added to the raw materials of the shimmer eggshell glaze, and the speed is maintained to continue grinding for 9 hours, and the glaze is sieved and iron is removed with a magnetic iron remover to prepare a shimmer eggshell glaze slurry;
[0113] S13, preparing the shimmering eggshell bottom glaze layer:
[0114] The surface of the green body is coated with a low-gloss eggshell base glaze slurry by glazing process. The glaze water specific gravity is 1.88g / mL and the glaze amount is 110g / m 2 , forming a shimmering eggshell enamel layer;
[0115] S14, preparing pattern layer:
[0116] The matte ink is sprayed on the surface of the shimmer eggshell base glaze layer by intelligent inkjet printing to form a pattern layer;
[0117] S15, preparing the shimmering eggshell protective glaze slurry:
[0118] The raw materials of the shimmer eggshell protective glaze are fully mixed and then placed in a ball mill. After grinding at a speed of 500 r / min for 2 hours, 42 wt% of water, 0.20 wt% of sodium carboxymethyl cellulose and 0.40 wt% of sodium tripolyphosphate accounting for the raw materials of the shimmer eggshell protective glaze are added. The speed is maintained and grinding is continued for 9 hours. A magnetic iron remover is used to remove iron to prepare a shimmer eggshell protective glaze slurry.
[0119] S16, preparation of shimmering eggshell protective glaze layer:
[0120] The glaze slurry is applied with eggshell protection on the surface of the pattern layer through the glaze spraying process. The glaze water specific gravity is 1.35g / mL and the glaze spraying amount is 350g / m 2 ;
[0121] S17, sintering:
[0122] The eggshell glaze with the shimmering effect is prepared by firing in a kiln at 1170° C. for 47 minutes.
[0123] Comparative Example 1
[0124] The difference between Comparative Example 1 and Example 1 is that the kaolin in Comparative Example 1 is not modified, and the other operations are the same.
[0125] Comparative Example 2
[0126] The difference between Comparative Example 2 and Example 1 is that the glass fiber in Comparative Example 2 is not modified by a silane coupling agent, and the other operations are the same.
[0127] Comparative Example 3
[0128] The difference between Comparative Example 3 and Example 1 is that the wollastonite in Comparative Example 3 is not modified, and the other operations are the same.
[0129] Performance Test:
[0130] 1. Anti-slip property: According to GT / B 377798-2019, the greater the friction coefficient, the more anti-slip;
[0131] 2. Wear resistance: According to GB / T3810.7-2016;
[0132] 3. Stain resistance: According to GB / T 3810.14-2016;
[0133] 4. Glossiness: The test standard adopts the method for measuring the mirror glossiness of building finishing materials (GB / T13891-2008). The test results are as follows:
[0134]
[0135] According to the above data, the glossiness of the eggshell glaze prepared in the examples is 4 to 5 degrees, showing a good shimmer effect. Compared with the comparative example, the examples have higher wear resistance and stain resistance, indicating better wear resistance and stain resistance, and the static friction coefficient of the examples is larger, indicating better anti-slip properties.
[0136] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A process for preparing eggshell glaze with a shimmering effect, characterized in that: The following steps are involved: S11. Green surface treatment: Grind the surface of the green body and control the temperature at 80~90℃; S12, preparing the glimmer eggshell base glaze slurry: According to weight percentage, the raw materials of the glimmering eggshell bottom glaze: 10-15% nepheline, 20-35% albite, 5-10% kaolin, 2-5% ball clay, 5-10% calcined alumina, 5-10% quartz, 15-25% potassium feldspar, 3% zinc oxide and 2-5% dolomite are mixed evenly and placed in a ball mill, and ground at a speed of 400-500 r / min for 1-2 hours, and then 42wt% of water, 0.20wt% of sodium carboxymethyl cellulose and 0.40wt% of sodium tripolyphosphate accounting for the raw materials of the glimmering eggshell bottom glaze are added, and the speed is maintained to continue grinding for 7-9 hours, and the sieving is performed and the iron is removed by a magnetic iron remover to prepare the glimmering eggshell bottom glaze slurry; S13, preparing the shimmering eggshell bottom glaze layer: The surface of the green body is coated with a low-gloss eggshell base glaze slurry by a glazing process. The glaze water specific gravity is 1.82~1.88g / mL and the glazing amount is 80~110g / m 2 , forming a shimmering eggshell enamel layer; S14, preparing pattern layer: The matte ink is sprayed on the surface of the shimmer eggshell base glaze layer by intelligent inkjet printing to form a pattern layer; S15, preparing the shimmering eggshell protective glaze slurry: The raw materials of the glimmer eggshell protective glaze are fully mixed by weight percentage: albite 15-20%, potassium feldspar 15-20%, modified kaolin 7-14%, zinc oxide 3-5%, dolomite 5-8%, low-temperature frit 10-15%, modified wollastonite 10-13%, strontium carbonate 5-10% and barium carbonate 10-15%, and then placed in a ball mill, and ground at a speed of 400-500r / min for 1-2h, and then 42wt% of water, 0.20wt% of sodium carboxymethyl cellulose and 0.40wt% of sodium tripolyphosphate accounting for the raw materials of the glimmer eggshell protective glaze are added, the speed is maintained and the grinding is continued for 7-9h, and a magnetic iron remover is used to remove iron to prepare a glimmer eggshell protective glaze slurry; S16, preparation of shimmering eggshell protective glaze layer: The glaze slurry is applied with a micro-gloss eggshell protective glaze slurry on the surface of the pattern layer through the glaze spraying process. The glaze water specific gravity is 1.25~1.35 g / mL and the glaze spraying amount is 250~350g / m 2 ; S17, Sintering: Firing in a kiln at 1150-1170° C. for 43-47 minutes to prepare the eggshell glaze with a shimmering effect; In step S15, the preparation process of the modified wollastonite is as follows: S21, treating the glass fiber by irradiation; S22, adding glass fiber to an aqueous solution containing 5% by mass of a silane coupling agent, stirring and mixing, soaking at 50-55° C. for 10-15 min, taking out, filtering and drying, and obtaining modified glass fiber; S23, mixing wollastonite and modified glass fiber in a mass ratio of (10-11): (1-3), heating to 70-80°C, stirring at a speed of 350-450 r / min for 4-5 hours, drying with hot air at 90-100°C for 11-15 hours, and grinding with a ball mill at a speed of 400 r / min for 3-4 hours to obtain the modified wollastonite; In step S15, the preparation process of the modified kaolin is as follows: S31, at a temperature of 70-80° C., ultrasonically dispersing kaolin and water at a power of 200-300 W to obtain a kaolin dispersion; S32, adjusting the pH of the kaolin dispersion to 7.5-8.5 with an organic base; S33, continue to add castor oil alkyd resin, wherein the mass ratio of kaolin, water and castor oil alkyd resin is (4-6):11:(2-4), raise the temperature to 80-90°C, continue stirring for 2-3 hours, let stand for aging for 10 hours, dry for 3-5 hours, then raise the temperature to 240-260°C and keep warm for 2-3 hours, cool to 60°C and place in a planetary ball mill for ball milling, and pass through a 600-mesh sieve to obtain the modified kaolin.
2. The process for preparing the eggshell glaze with a micro-gloss effect according to claim 1, characterized in that: In step S15, the chemical composition of the low-temperature frit is: SiO2: 54.6%, Al2O3: 12.01%, CaO: 6.85%, MgO: 4.57%, K2O: 5.18%, Na2O: 2.08%, ZnO: 6.34%, BaO: 8.37%.
3. The process for preparing the eggshell glaze with a micro-gloss effect according to claim 1, characterized in that: In step S21, the irradiation power of the irradiation treatment is 350-450W, and the irradiation time is 1-2h.
4. The process for preparing the eggshell glaze with a micro-light effect according to claim 1, characterized in that: In step S22, the silane coupling agent is one of KH-570, KH-792, and DL-602.
5. The process for preparing the eggshell glaze with a micro-light effect according to claim 1, characterized in that: In step S22, the solid-to-liquid ratio of the glass fiber to the aqueous solution of the silane coupling agent is 1:10 g / mL.
6. The process for preparing the eggshell glaze with a low-gloss effect according to claim 1, characterized in that: In step S32, the organic base is one of triethylamine and pyridine.
Citation Information
Patent Citations
Digital satin protection glaze and product and preparation method thereof
CN115849713A
Wear-resistant non-stick ceramic pot and preparation method thereof
CN118216807A
Eggshell glaze, high-whiteness glazed tile and preparation method thereof
CN118495812A